The observed and modelled influence of the Madden–Julian Oscillation on East African rainfall. (30th October 2014) - Hogan, Emily; Shelly, Ann; Xavier, Prince
ABSTRACT The aim of this work is to determine to what extent precipitation modulated by the Madden–Julian Oscillation (MJO) over East Africa can be forecast by the operational global Met Office Unified Model (MetUM). Observed patterns of rainfall were analysed over Kenya, Tanzania and Uganda and used to validate MetUM forecasts made over the period 2005–2012. It was found that there is a large seasonal dependence on the MJO for episodes of enhancement and suppression of rainfall over the inland highlands and the coastal lowlands, particularly from March to May and October to December, when the Intertropical Convergence Zone is located directly over the region. In phases 2–4 of the MJO lifecycle, there is an enhancement of precipitation over the highland regions and suppression over the coast. This dipole is reversed throughout phases 6–8. These findings corroborate previous studies undertaken over the region. The observed patterns were replicated well by the MetUM global model, even up to a forecast lead time of 5 days (T + 120 h), though some minor drift is apparent and convective and suppressed centres tend to stray from those of the observed rainfall. Model resolution is thought to be a key component of this difference. The systematic errors will likely improve with further plans for model resolution and physics upgrades, although the overall quality of the MetUM's ability to forecast the MJO over this region is sound.